2013
DOI: 10.1002/clc.22213
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Race/Ethnicity With Door‐to‐Balloon Time and Mortality in Patients Undergoing Primary Percutaneous Coronary Intervention for ST‐Elevation Myocardial Infarction: Findings From Get With the Guidelines–Coronary Artery Disease

Abstract: Background: Prior studies have described racial/ethnic disparities in door-to-balloon (DTB) time for patients undergoing primary percutaneous coronary intervention (PCI). We sought to compare DTB time between different racial/ethnic groups undergoing primary PCI for ST-elevation myocardial infarction in Get With the Guidelines (GWTG). Hypothesis: There may be differences in D2B time associated with race/ethnicity. Methods: We identified 7445 patients undergoing primary PCI: white (n = 6365), African American (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 22 publications
5
59
0
Order By: Relevance
“…21 Similarly, in STEMI patients undergoing primary PCI as part of the GWTG study, investigators found no association between race/ethnicity and in-hospital mortality. 13 In the analysis of 12 555 AMI patients in New York City, Hispanics were more likely to survive than whites, and among patients who were not revascularized, Hispanics were more likely to survive and be discharged than whites. 3 Having preexisting complications may worsen outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…21 Similarly, in STEMI patients undergoing primary PCI as part of the GWTG study, investigators found no association between race/ethnicity and in-hospital mortality. 13 In the analysis of 12 555 AMI patients in New York City, Hispanics were more likely to survive than whites, and among patients who were not revascularized, Hispanics were more likely to survive and be discharged than whites. 3 Having preexisting complications may worsen outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…12 In STEMI patients undergoing primary PCI as part of the GWTG study, median door-toballoon times were marginally, but not significantly, longer for Hispanic patients than for non-Hispanic white patients, and Hispanic ethnicity was not associated with reduced odds of door-to-balloon times ≤90 minutes (a quality-of-care indicator for treatment of STEMI). 13 In the ACTION Registry-GWTG study, use of acute medications and primary PCI was similar in Hispanic and non-Hispanic patient groups, 20 and Hispanic patients in the NYS-PCI-RS study were found to have higher rates of surgical or PCI revascularization. 22 Other studies show lower rates of revascularization for Hispanic patients.…”
Section: Treatment and Medicationmentioning
confidence: 97%
See 3 more Smart Citations